The Coming of the Spirit and the Laying on of Hands: A Paradigm for Ethnic Reconciliation - Adams, Scott Lewis (Journal of pentecostal theology, 2020)
The traditional Pentecostal understanding of the events of Acts 8.4-25 typically centers upon a two-stage model for the reception of the Spirit. While this article does not seek to preclude the plausibility of such a model, it does, however, seek to take a step further by providing a culturally-sensitive analysis concerning how the coming of the Spirit, the apostolic imposition of hands (Acts 8.17), and the concept of worship in spirit and truth' (Jn 4.24) serves as a paradigm for ethnic reconciliation.